PENGARUH LOKASI USAHA TERHADAP KEUNTUNGAN (STUDI KASUS TOKO PAKAIAN DI KECAMATAN BANTAN KABUPATEN BENGKALIS) - Sandi Andika; Lukluil Mukarromah (Magister Manajemen STIE Bank BPD Jateng, 2021)
Various factors that cause success in the business carried out by entrepreneurs, one of which is the location of the business. The right business location will certainly have a positive impact on the sustainability and profits of thebusiness. This study aims to determine the effect of business location on profits. The subjects in this study wereclothing store business owners who opened a business in Bantan District with a total of 23 shops, so theresearchers used total sampling. This type of research is field research with quantitative research methods. Data collection techniques used are observation, questionnaires or questionnaires, and documentation. Based on theresults of data analysis, it can be concluded that the correlation coefficient can be stated that there is a positive relationship between the business location variable and the profit variable which is categorized as